2020
DOI: 10.1074/jbc.ra120.012753
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor HAND2 up-regulates transcription of the IL15 gene in human endometrial stromal cells

Abstract: Cyclic changes of the human endometrium, such as proliferation, secretion, and decidualization, occur during regular menstrual cycles. Heart– and neural crest derivatives–expressed transcript 2 (HAND2) is a key transcription factor in progestin-induced decidualization of human endometrial stromal cells (ESCs). It has been suggested that HAND2 regulates interleukin 15 (IL15), a key immune factor required for the activation and survival of uterine natural killer (uNK) cells. Activated uNK cells can promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 43 publications
1
46
1
Order By: Relevance
“…In addition, we extracted and analyzed all the genes in the MEturquoise module and found five important genes ( HAND2 , LMO1 , MYH11 , MYLK and FHL1 ) which accounted for a significantly higher proportion in the IM-H subtype. HAND2 can regulates interleukin 15 (IL15), a key immune factor required for the activation and survival of uterine natural killer (uNK) cells [ 41 ]. LMO1 overexpression in GC could be as one of new markers of poor prognosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we extracted and analyzed all the genes in the MEturquoise module and found five important genes ( HAND2 , LMO1 , MYH11 , MYLK and FHL1 ) which accounted for a significantly higher proportion in the IM-H subtype. HAND2 can regulates interleukin 15 (IL15), a key immune factor required for the activation and survival of uterine natural killer (uNK) cells [ 41 ]. LMO1 overexpression in GC could be as one of new markers of poor prognosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We found that, like HAND2, IL15 decreases throughout gestation and both genes increase in expression as the menstrual cycle progresses. Unexpectedly however, while previous studies showed that HAND2 induces IL15 in DSCs (Shindoh et al ., 2014; Murata et al ., 2020), we discovered that HAND2 inhibited IL15 expression in ESFs, indicating a switch in regulatory activity sometime during early menstrual cycle. These data suggest that HAND2 regulates the appropriate timing of endometrial IL15 expression during the menstrual cycle and pregnancy, and thus the appropriate timing of uNK cell recruitment, trophoblast migration and the clearance of senescent endometrial stromal cells from the implantation site ( Figure 5D ).…”
Section: Discussionmentioning
confidence: 99%
“…Decidualization is driven by increases in P4 and then local cyclic adenosine monophosphate (cAMP) production [ 8 , 9 ]. In the human endometrium after ovulation, ESCs transform from fibroblast-like cells in the proliferative phase to epithelium-like cells with cytoplasmic expansion, large pale nuclei, and rounded shapes in the secretory phase [ 10 ] ( Figure 1 ), a process that involves complex cytoskeletal rearrangements [ 11 ]. The phosphorylation of myosin light chain and concentrated F-actin induce the intracellular remodeling and resulting morphological changes [ 12 , 13 , 14 ].…”
Section: Decidualization: Morphological Differentiation In the Hummentioning
confidence: 99%
“…Several studies indicate that IL-15 plays various important roles in NK cell biology via binding these receptors [ 88 ]. Previous quantitative polymerase chain reaction (PCR) studies show that IL15 expression is significantly higher during the secretory phase in the human endometrium [ 10 , 25 ]. Histological analysis using human endometrial tissues also indicates that IL15 increases in the secretory phase [ 10 ] and is observed in many ESCs in the endometrium during this phase [ 10 ].…”
Section: Il-15mentioning
confidence: 99%
See 1 more Smart Citation